Gold and organocatalysis combined - Hashmi, A. Stephen K.; Hubbert, Christoph (Angewandte Chemie. International edition, 2010)
All that glitters: Binary catalytic systems of gold(I) complexes and chiral Brønsted acids, which were recently reported by the research groups of Dixon and Gong, represent a significant leap forwards in the area of sequential one-pot reactions. The special feature of these reactions is the isolobal analogy of the proton and [LAuI] cations, which requires a delicate balance between the reactivities of the acids and the gold complexes.